Elective nodal radiotherapy with a gapless radiation field junction for oligorecurrent prostate cancer after previous radiotherapy. (March 2023) - Li, Minglun; Fan, Yourong; Trapp, Christian; Schmidt-Hegemann, Nina Sophie; Ma, Jing; Buchner, Alexander; Lu, Shun; Xu, Bin; Stief, Christian; Wang, Xuanbin; Zhou, Cheng; Belka, Claus; et al.
Highlights: A gapless junction of an elective nodal radiotherapy field after previous radiotherapy is feasible. A cumulative maximum dose (Dmax-cum ) ≤ 95 Gy and a maximum cumulative dose in 1 cc (D1cc-cum ) < 90 Gy were used as dose constraints. This approach is safe without additional acute or late grade 3 toxicity. Abstract: Purpose: To evaluate the feasibility of subsequent elective nodal radiotherapy (ENRT) for nodal recurrences after previous radiotherapy with a defined planning approach for a gapless radiation field junction. Methods: Patients with 1) previous radiotherapy of prostate or prostatic fossa and subsequent pelvic ENRT or 2) previous pelvic radiotherapy and subsequent ENRT to paraaortic lymph nodes (LN) and gapless junction of both radiation fields were analyzed. The cumulative maximum dose (Dmax-cum ) and the maximum cumulative dose in 1 cc (D1cc-cum ) were estimated. Absolute toxicity and the toxicity exceeding baseline were evaluated. Results: Twenty-two patients with PSMA-PET/CT-staged nodal oligorecurrence after prior radiotherapy were treated with pelvic (14 patients) or paraaortic ENRT (9 patients). One patient was treated sequentially at both locations. Median time between first and second RT was 20.2 months. Median doses to the lymphatic pathways and to PET-positive LN were 47.5 Gy and 64.8 Gy, respectively. The planning constraint of an estimated Dmax-cum ≤ 95 Gy and of D1cc-cum < 90 Gy were achieved in 23/23 cases and 22/23 cases, respectively. Median follow-up was 33.5 months. There was no additional acute or late toxicity ≥ grade 3. Worst acute toxicity exceeding baseline was grade 1 in 68.2% and grade 2 in 22.7% of patients. Worst late toxicity exceeding baseline was grade 1 in 31.8% and grade 2 in 18.2% of patients. Conclusion: ENRT for nodal recurrences after a previous radiotherapy with gapless junction of radiation fields seems to be feasible, applying the dose constraints Dmax-cum ≤ 95 Gy and D1cc-cum < 90 Gy without grade 3 acute or late toxicities exceeding baseline.